ANALYSIS OF LOAD CAPACITY, WEAR AND LIFE WORM TRANSMISSION WITH INVOLUTE WORM CORRECTED WITH TWO- AND TREE PAIR ENGAGEMENT - Чернець, Мирон Васильович; Кіндрачук, Мирослав Васильович; Опеляк, Марек; Костецький, Іван Володимирович (Problems of Friction and Wear, 2019)
The paper presents a method for determining the effect of teeth correction in an involute worm gear on the contact strength, wear and life of teeth of the worm wheel. The cases of two- and three-pairy of engagement are considered. The regularities regarding the effect of correction on contact and tribocontact parameters are established. When a positive correction coefficient is applied, the maximum contact pressures and wheel teeth wear decrease while the gear life increases; when the correction coefficient is negative, the trend is opposite.